Kontribusi Budidaya Keramba Jaring Apung terhadap Peningkatan Faktor Pembatas Fosfor dan Nitrogen di Ekosistem Waduk Pulau Jawa - Prasetya, Indra Sindhu; Nugrayani, Dewi; Safitri, Ayu Putri; Abrilia, Maulita (MAIYAH, 2023)
Floating net cage (KJA) cultivation activities have had a significant impact on the community, especially in terms of providing food, increasing employment opportunities and economic growth in the surrounding area. However, we need to realize that KJA has negative impacts that can affect water quality and community activities. Article reviews aims to determine the contribution of phosphorus and nitrogen as limiting factors in reservoir ecosystems due to floating net cages and identify methods that can reduce their negative impacts. KJA activities cause an increase in excessive accumulation of phosphorus and nitrogen in reservoir waters, which comes from food waste and fish metabolism. In addition, the KJA population that fills the reservoir's capacity provides a significant contribution to this increase. The impact of this accumulation is an increased potential for eutrophication, which can damage aquatic ecosystems by causing excessive growth of algae and air plants and decreasing water quality. This is a serious problem that can endanger fisheries cultivation in reservoir waters. Therefore, there are various strategies that can be implemented. This includes implementing stricter regulations regarding KJA practices, educational efforts for cultivators, as well as anti-collaboration between stakeholders (pentahelix). Therefore, the use of cleaning organisms and the use of innovative technology can also be an effective solution in preserving the aquatic environment.